Vairimorpha (Nosema) ceranae can promote Serratia development in honeybee gut: an underrated threat for bees? - Braglia, Chiara; Alberoni, Daniele; Garrido, Paula Melisa; Porrini, Martin Pablo; Baffoni, Loredana; Scott, Dara; Eguaras, Martin Javier; Di Gioia, Diana; Mifsud, David (Frontiers in Cellular and Infection Microbiology, 2024)
The genus Serratia harbors opportunistic pathogenic species, among which Serratia marcescens is pathogenic for honeybees although little studied. Recently, virulent strains of S. marcescens colonizing the Varroa destructor mite's mouth were found vectored into the honeybee body, leading to septicemia and death. Serratia also occurs as opportunistic pathogen in the honeybee's gut with a low absolute abundance. The Serratia population seems controlled by the host immune system, but its presence may represent a hidden threat, ready to arise when honeybees are weakened by biotic and abiotic stressors.To shed light on the Serratia pathogen, this research aims at studying the Serratia's development dynamics in the honeybee body, and its interactions with the co-occurring fungal pathogen Vairimorpha ceranae. Firstly, the degree of pathogenicity and the ability to permeate the gut epithelial barrier of 3 Serratia strains, isolated from honeybees and belonging to different species (S. marcescens, Serratia liquefaciens and Serratia nematodiphila), was assessed by artificial inoculation of newborn honeybees with different Serratia doses (10 4 , 10 6 and 10 8 cells/ml). The absolute abundance of Serratia in the gut and in the haemocoel was assessed in qPCR with primers targeting the luxS gene. Moreover, the absolute abundance of Serratia was assessed in the gut of honeybees infected with V. ceranae at different development stages and supplied with beneficial microorganisms and fumagillin.Our results showed that all tested Serratia strains could pass through the gut epithelial barrier and proliferate in the haemocoel; however, the S. marcescens strain resulted to be the most pathogenic.Moreover, in cage conditions, Serratia better proliferates when a V. ceranae infection is co-occurring, with a positive and significant correlation. Finally, fumagillin and some of the tested beneficial microorganisms could control both Serratia and Vairimorpha development. Our findings suggest a correlation between the two pathogens in laboratory condition.